The influence of metacognitive strategies on students’ mathematical connection abilities and learning independence - Hasibuan, Nurleli; Firmansyah, Firmansyah; Panjaitan, Dedy Juliandri; Zahari, Cut Latifah (Mahesa Research Center, 2025)
Mathematical connection skills and learning independence remain challenges in the formal education system, particularly among students who rely heavily on procedural memorization rather than deep conceptual understanding. This situation underscores the necessity of developing learning strategies that promote critical thinking awareness and reflection. One such strategy is the application of metacognitive techniques. This study seeks to assess the impact of metacognitive strategies on the development of mathematical connection skills and learning independence among eighth-grade students enrolled in the mathematics department at Al Washliyah Hamparan Perak Private Middle School. Employing a quantitative approach with a quasi-experimental pretest-posttest control group design, the study sample comprises two classes: an experimental group that receives instruction utilizing metacognitive strategies and a control group that receives conventional instruction. The analysis of the data revealed a substantial positive impact of metacognitive strategies on both mathematical connection skills and learning independence. Specifically, the experimental group demonstrated a significant improvement in mathematical connection skills (significance 0.000 < 0.05) and learning independence (significance 0.001 < 0.05). The average gain score for mathematical connections was 0.54735 for the experimental group and 0.28264 for the control group. Similarly, the average gain score for learning independence was 0.39870 for the experimental group and 0.19518 for the control group. Consequently, metacognitive strategies have been demonstrated to be an effective tool for enhancing both mathematical connection skills and learning independence. Their implementation in the formal education system is crucial in fostering critical thinking, self-awareness, and independent learning among students.